GENDERED CHALLENGES TO PSYCHOLOGY’S AUTHORITY - Lempert, Lora Bex (PINS-Psychology in Society, 2025)
Shefer, T, Boonzaier, F & Kiguwa, P (eds) (2006) The gender of psychology. Cape Town: UCT Press. ISBN 1-9197-1392-1 pbk. Pages xx + 335. The gender of psychology, the first psychology text on gender published in South Africa, is a stunning, theoretically and often analytically sophisticated text with wide ranging feminist considerations of gender, the psychology of gender, and, uniquely in this collection, the gender of psychology as conceptualized and practiced in South Africa. The text includes informed discussions of both historical and contemporary psychological theorizing on gendered intersections with other social categories and epistemological positions (race, class, ethnicity, sexualities, and so on), and on the feminist challenges that destabilize these conventional disciplinary notions within the South African context.